2021
DOI: 10.1177/1948550620983051
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Interplay Between Race, Work Ethic Stereotypes, and Attitudes Toward Welfare Recipients and Policies

Abstract: The current research investigates the role of racialized work ethic stereotypes on attitudes toward welfare. We hypothesized that work ethic stereotypes shape both people’s attitudes toward welfare and their perceptions of who benefits from these policies. Consistent with hypotheses, when the demographic composition of welfare recipients was majority Black (vs. White), participants thought recipients were lazier and were less positive to welfare programs and policies (Study 1). Describing welfare recipients as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…To our knowledge, no formal power analysis procedures exist for the image-generation phase in reverse-correlation paradigms (see also Brown-Iannuzzi, Cooley, Marshburn, McKee, & Lei, 2021). Thus, we set our target sample size for the image-generation experiment using a heuristic of at least 60 participants per cell in a 2 × 2 between-subjects design; data were collected until this target number was surpassed.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, no formal power analysis procedures exist for the image-generation phase in reverse-correlation paradigms (see also Brown-Iannuzzi, Cooley, Marshburn, McKee, & Lei, 2021). Thus, we set our target sample size for the image-generation experiment using a heuristic of at least 60 participants per cell in a 2 × 2 between-subjects design; data were collected until this target number was surpassed.…”
Section: Participantsmentioning
confidence: 99%
“…Decomposing the interaction differently, the outgroup CIs generated by perspective takers (M = 3.39, SD = 1.15) were rated as more likable than were the outgroup CIs generated by control participants (M = 3.07, SD = 1.20), t(136) = 2 In all the image-assessment experiments, we conducted analyses reported in the main text at the level of the participant (i.e., image rater) by collapsing across CIs, rather than at the level of the CI by collapsing across image raters. This analysis strategy is the only one reported in studies using subgroup CIs (Brown-Iannuzzi et al, 2021;Cone et al, 2020); however, both analysis strategies have been reported in studies using individual CIs. Notably, Cone et al (2020) conducted their analyses at the level of the individual CI.…”
Section: Subgroup Cis (Experiments 1a)mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, because laziness stereotypes about the poor may justify opposition toward policies aimed at helping the poor, such as welfare policies (Brown-Iannuzzi et al, 2021; Bryan et al, 2009; Cooley, Brown-Iannuzzi, & Boudreau, 2019; see also McCoy & Major, 2007; Savani & Rattan, 2012), within-group status comparisons may play a unique role in White Americans’ welfare attitudes. Namely, White Americans who feel left behind by their racial group may be more likely to think welfare recipients are hardworking and, in turn, may be more likely to support welfare policies.…”
Section: Within-group Status Comparisons Among White Americansmentioning
confidence: 99%
“…As stated in the preceding text, our research program explores the interplay of race/class stereotypes (Brown-Iannuzzi, Dotsch, et al, 2017, 2019, 2021; Cooley, Brown-Iannuzzi, & Boudreau, 2019; Cooley, Brown-Iannuzzi, Lei, et al, 2019; Cooley et al, 2020), subjective perceptions of status (Brown-Iannuzzi et al, 2014, 2015, 2020; Cooley et al, 2020), and racial privilege (Cooley, Brown-Iannuzzi, & Cottrell, 2019; Cooley, Brown-Iannuzzi, Lei, et al, 2019). Thus, the purpose of the final study was two-fold: (a) investigate whether ownership of racial privilege may shift perceptions of within-group status and (b) investigate the consequences of such a shift on laziness stereotypes of welfare recipients and support for welfare policies.…”
Section: Studymentioning
confidence: 99%